Evaluation of Pandanrejo website content using a copywriting approach in Pandanrejo Tourism Village, Central Java - Nurdin Hidayah; Sugeng Hermanto; Herlan Suherlan; Rachmat Syam; Raden Fajar Widiarrachman (Universitas Merdeka Malang, 2023)
The website is a media that acts as the backbone of digital marketing in a tourism village. As the spearhead of digital media and sales channels, the tourism village website must always be optimized so that it always has a high conversion rate. Copywriting is a technique for writing content in digital media that is widely used practically in increasing conversion rates. This study aims to evaluate the Pandanrejo Tourism Village website as an information base for formulating conversion rate optimization (CRO) at a later stage. This study uses a qualitative approach with several collection methods, namely by conducting interviews with website managers, copywriting experts and website-based information system experts, making direct observations of the Pandanrejo’s website, and reviewing the literature. To produce valid information and results, the data was analyzed by confirming between informants and references to the literature. The results obtained from this study indicate that the Pandanrejo Tourism Village website content does not yet have a touch of copywriting elements through the AIDA formula.